Cellular and molecular mechanisms of NiONPs toxicity on eel hepatocytes HEPA-E1: An illustration of the impact of Ni release from mining activity in New Caledonia. (September 2022) - Germande, Ophélie; Beaufils, Fabien; Daffe, Guillemine; Gonzalez, Patrice; Mornet, Stéphane; Bejko, Megi; Errera, Marie-Hélène; Lacomme, Sabrina; Gontier, Etienne; Guibert, Christelle; Baudrimont, Isabelle; Baudrimont, Magalie
Abstract: Anthropic activities such as open pit mining, amplify the natural erosion of metals contained in the soils, particularly in New Caledonia, leading to atmospheric emission of nickel oxide nanoparticles (NiONPs). These particles are produced during extraction end up in aquatic ecosystems through deposition or leaching in the rivers. Despite alarming freshwater Ni concentrations, only few studies have focused on the cellular and molecular mechanisms of NiONPs toxicity on aquatic organisms and particularly on eels. Those fish are known to be sensitive to metal contamination, especially their liver, which is a key organ for lipid metabolism, detoxification and reproduction. The objective of this study was to assess in vitro the cytotoxic effects of NiONPs on Anguilla japonica hepatocytes, HEPA-E1. HEPA-E1 were exposed to NiONPs (0.5–5 μg/cm 2 ) for 4 or 24 h. Several endpoints were studied: (i) viability, (ii) ROS production, SOD activity and selected anti-oxidant genes expression, (iii) inflammation, (iv) calcium signalling, (v) mitochondrial function and (vi) apoptosis. The results evidenced that NiONPs induce a decrease of cell viability and an increase in oxidative stress with a significant superoxide anion production. An increase of mitochondrial calcium concentration and a decrease of mitochondrial membrane potential were observed, leading to apoptosis. These results underline the potential toxic impact of NiONPs on eels living in mining areas. Therefore, eel exposure to NiONPs can affect their migration and reproduction in New Caledonia. Graphical abstract: Image 1 Highlights: NiONPs decrease cell viability and induce a ROS overproduction in eel hepatocytes. Oxidative stress leads to a [Ca2+] rise and a pro-inflammatory response in HEPA-E1. In mitochondria, NiONPs induce ROS generation, ѰMP collapse and Ca 2+ overload. NiONPs adverse effects could compromise lipid metabolism and reproduction of eels.